Method for producing solid sulfide electrolyte
By using low-energy mixing steps and heat treatment methods in the production of sulfide electrolytes, the problem of high-energy grinding limiting large-scale production is solved, and high purity and high conductivity sulfide electrolyte production is achieved.
Patent Information
- Application Number
- JP2024565327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-05-08
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art requires a high-energy grinding process when producing sulfide electrolytes, limiting the feasibility of large-scale production.
By providing a method of providing a solid electrolyte precursor mixture containing LiX, a low energy mixing step is employed instead of a high energy grinding step, followed by heat treatment to obtain a sulfide electrolyte with a sulfur-silver-silver sulfide crystal structure.
The production of high-purity sulfide electrolyte without high energy grinding is achieved, which improves production efficiency and has high ionic conductivity of the sulfide electrolyte.
Smart Images

Figure 2025514541000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a solid sulfide electrolyte and a solid sulfide electrolyte obtained by the method. [Background technology]
[0002] As the development of small and lightweight electronic products, electronic devices, communication devices, etc. progresses rapidly and the need for electric vehicles to address environmental issues becomes more prominent, there is a demand for improved performance of secondary batteries used as power sources for these products. In particular, lithium secondary batteries have been attracting attention as high-performance batteries due to their high energy density and high reference electrode potential.
[0003] However, the electrolytes conventionally used in lithium secondary batteries are liquid electrolytes, such as organic solvents, and therefore may persistently cause safety problems, such as electrolyte leakage and fire hazards.
[0004] Recently, solid-state batteries that include solid electrolytes rather than liquid electrolytes have been used to improve the safety characteristics of lithium secondary batteries and have attracted much attention, for example, solid electrolytes are typically safer than liquid electrolytes due to their non-flammable or flame-retardant nature.
[0005] The solid electrolyte may include oxide-based solid electrolytes, polymer-based electrolytes, and sulfide-based electrolytes. Sulfide-based electrolytes, such as sulfide-based solid electrolytes having an argyrodite crystal structure, are commonly used due to their higher lithium ion conductivity range compared to oxide-based and polymer-based solid electrolytes.
[0006] Conventionally, powder Li 2 S, P 2 S 5A method for producing sulfur-based solid electrolytes has been used using a mixture obtained by grinding and vitrifying sulfide and lithium halides, such as LiCl or LiBr. In this conventional method for producing solid electrolytes, a high-energy grinding process followed by a heat treatment step (i.e., a calcination step) is required to convert the mixture of powders into a sulfide-based electrolyte with a germanite structure. However, this high-energy grinding step has the disadvantage of requiring a large amount of energy, which limits the scale-up of the process for mass production of sulfide-based electrolytes. An example of this high-energy grinding step is ball milling or mechanical grinding of the starting material. US Patent Application Publication No. 2019 / 0198917 (A1), US Patent Application Publication No. 2020 / 0028207 (A1) and US Patent Application Publication No. 2020 / 0385131 (A1) describe this high-energy grinding method for producing sulfide-based electrolytes. High-energy ball milling uses grinding speeds from 200 rpm to 1200 rpm and even higher.
[0007] Therefore, there is a need to provide a method for producing a solid sulfide electrolyte that requires less energy input and can be scaled up for mass production of solid sulfide electrolyte.
[0008] An object of the present invention is to provide a method for producing a solid sulfide electrolyte.
[0009] A further object of the present invention is to provide a solid sulfide electrolyte obtainable from said method.
[0010] It is a further object of the present invention to provide a solid-state lithium battery comprising the solid sulfide electrolyte. Summary of the Invention
[0011] In a first aspect, the object of the present invention is to provide a method for the preparation of a Li 2 S., Li 3 P.S. 4This is accomplished by providing a method for producing a solid sulfide electrolyte by providing a solid electrolyte precursor mixture comprising LiX and LiX.
[0012] The present inventors have surprisingly found that Li 2 S., Li 3 P.S. 4 We have found that by mixing a solid electrolyte precursor mixture containing LiX, such as LiCl, and LiCl, a high-energy milling step is not required to prepare a solid sulfide electrolyte. As demonstrated in the accompanying examples, a low-energy mixing step is sufficient to prepare a solid electrolyte mixture, which after being subjected to a heat treatment, results in a solid electrolyte having high purity and an argyranthrene crystal structure. In contrast, we have found that a high-energy milling step is sufficient to prepare a solid electrolyte precursor mixture containing LiX, such as LiCl, and LiCl, which after being subjected to a heat treatment, results in a solid electrolyte having high purity and an argyranthrene crystal structure. 2 S, P 2 S 5 and LiCl, followed by heat treatment, does not provide a solid sulfide electrolyte with arginite crystal structure of sufficient purity: the solid mixture still contains a large amount of unreacted starting material that is detrimental to the ionic and / or electronic conductivity of the overall mixture.
[0013] Li 2 S and P 2 S 5 Departing from Li 3 P.S. 4 The in situ formation of Li has been reported (Jiang, H. et al, Ionics 2020, 26, 2335-2342). However, the present inventors have 2 SP 2 S 5 Li instead of a mixture of 3 P.S. 4 Starting from this, we clearly demonstrate that a low-energy process can be used to obtain solid sulfide electrolytes with argyrgentite crystal structure with higher purity and at the same time higher ionic conductivity.
[0014] Without being bound by any theory, the inventors used P 2 S5 By using Li as the starting material, 3 P.S. 4 By using Li 6 P.S. 5 We believe that more energy is required for the formation of Cl. 2 S 5 has an adamantane-like crystal structure, and therefore is different from Li, which has a cubic crystal structure. 6 P.S. 5 It is speculated that more energy is required to split or destroy the crystal structure to form Cl. In contrast, Li, which has an orthorhombic crystal structure, 3 P.S. 4 By using 6 P.S. 5 It is believed that less energy is required to transform it into Cl.
[0015] In a further aspect, the present invention provides a solid sulfide electrolyte obtainable by the process according to the present invention.
[0016] In a further aspect, the present invention provides a solid-state battery comprising a solid sulfide electrolyte obtainable by the method according to the present invention. [Brief description of the drawings]
[0017] [Figure 1] XRD spectrum of the dome sample holder. [Diagram 2] 1 is an XRD spectrum of the heat-treated solid sulfide electrolyte of Example 1. [Diagram 3] 1 is an XRD spectrum of the heat-treated solid sulfide electrolyte of Example 2. [Figure 4] 1 is an XRD spectrum of the heat-treated solid sulfide electrolyte of Example 3. [Diagram 5] 1 is a first charge-discharge curve of Example 4. [Figure 6] 1 is a rate capability test of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In order to enable the practice of the invention, preferred embodiments are described in detail in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. On the contrary, the invention encompasses numerous alternatives, modifications and equivalents, as will become apparent from a consideration of the following detailed description and the accompanying drawings.
[0019] The term "comprising" as used in the present specification and claims should not be interpreted as being limited to the means recited thereafter, nor does it exclude other elements or steps. It should be interpreted as specifying the presence of the recited features, integers, steps, or ingredients as mentioned, but without excluding the presence or addition of one or more other features, integers, steps, or ingredients, or groups thereof. Thus, the scope of the expression "a composition comprising components A and B" should not be limited to a composition consisting of components A and B only. It means that in the context of the present invention, the only relevant components of the composition are A and B. Thus, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".
[0020] As used herein, the term "solid-state battery" refers to a cell or battery that contains only solid or substantially solid components, such as solid electrodes (e.g., anodes and cathodes) and solid electrolytes.
[0021] As used herein, the term "argyrrhizite crystal structure" refers to the naturally occurring Ag 8 GeS 6 and Li 7 S 6(argyrrhizite) refers to a crystal structure having a similar crystal structure or system to that of Argentargite. Argentargite-type crystals may be orthorhombic with a Pna21 space group and a unit cell of a=15.149, b=7476, c=10589 [Å], and Z=4. In some embodiments, the Argentargite-type crystal structure may also be empirically determined by X-ray diffraction spectroscopy, for example, by observing peaks at about 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1°, and 32±1° using CuKα radiation.
[0022] Ionic conductivity referred to herein refers to ionic conductivity determined by electrochemical impedance spectroscopy (EIS) at 25°C. It is preferably determined using ion-blocking electrodes on cold-pressed samples densified at 125°C and 350 MPa for 5 minutes, after which the ionic conductivity was measured at 25°C under a working pressure of 125 MPa. Preferably, an excitation voltage of 10 mV was applied in the frequency range of 7 MHz to 1 Hz, and the data was interpreted by equivalent circuit analysis. A suitable conductivity analyzer is a potentiostat with a frequency analyzer such as those available from Biologic.
[0023] Electronic conductivity referred to herein refers to electronic conductivity determined at 25° C. It is preferably determined using ion-blocking electrodes on hot-pressed samples densified at 125° C. and 350 MPa for 5 minutes, after which electronic conductivity was measured at 25° C. under a working pressure of 125 MPa. Preferably, electronic conductivity was measured by step potentiostatic polarization at 0.2 V, 0.4 V and 0.6 V for 20 minutes. A suitable conductivity analyzer is a potentiostat with a frequency analyzer, such as that available from Biologic.
[0024] X-ray diffraction (XRD) spectroscopy as referred to herein refers to XRD experiments carried out using a Panalytical X'Pert Pro with a Cu Kα1 source (1.5405980 A or 8.05 keV). Preferably, the sample holder was an Anton Paar holder with a PEEK dome and the software used for analysis was Highscore.
[0025] Manufacturing method As described above, in a first aspect, the present invention provides a method for producing a solid sulfide electrolyte, comprising: Li 2 S., Li 3 P.S. 4 providing a solid electrolyte precursor mixture comprising LiX and LiX; mixing the solid electrolyte precursor mixture to obtain a solid electrolyte mixture; and heat treating the solid electrolyte mixture to obtain a solid sulfide electrolyte having a germanite crystal structure; wherein X is a halogen selected from F, Cl, Br, I, or combinations thereof.
[0026] The term "solid electrolyte precursor mixture" or "solid electrolyte mixture" as used herein refers to an electrolyte precursor mixture or electrolyte mixture that is essentially free of liquid. The term "essentially free of liquid" means that the solid electrolyte precursor mixture and / or solid electrolyte mixture contains less than 10 wt. % of liquid of the total weight of the solid electrolyte precursor mixture and / or solid electrolyte mixture, preferably less than 7.5 wt. %, more preferably less than 5 wt. %, even more preferably less than 2.5 wt. %, and most preferably less than 1 wt. % of the total weight of the solid electrolyte precursor mixture and / or solid electrolyte mixture. In a more preferred embodiment, the solid electrolyte precursor mixture and / or solid electrolyte mixture contains less than 1000 ppm of liquid of the total weight of the solid electrolyte precursor mixture and / or solid electrolyte mixture, preferably less than 500 ppm, more preferably less than 100 ppm, even more preferably less than 50 ppm, and most preferably less than 10 ppm of liquid of the total weight of the solid electrolyte precursor mixture and / or solid electrolyte mixture. In the context of the present invention, a liquid shall be considered to be an organic or aqueous compound that is liquid at standard conditions of temperature and pressure as defined by IUPAC. Hereby, the boiling and melting points are considered to be those at standard atmospheric pressure, i.e., 101325 Pa. As will be appreciated by those skilled in the art, the presence of organic liquids can be determined by thermogravimetric analysis (TGA) or nuclear magnetic resonance (NMR) spectroscopy, and the presence of aqueous liquids can be determined by Karl Fischer titration.
[0027] As will be appreciated by those skilled in the art, Li 3 P.S. 4 All crystal structures of Li 3 P.S. 4 The γ-, α- and β-polymorphs of can be used in the process of the invention.
[0028] In a preferred embodiment of the present invention, the solid sulfide electrolyte is represented by the formula (I): Li 7-y P.S. 6-y X y (I) In the method according to the present invention, y=0.8-1.7. As will be understood by those skilled in the art, when y is 0.8-1.7, it is possible to obtain a solid sulfide electrolyte having a germanite crystal structure. In a more preferred embodiment, y is 0.8-1.7, preferably 0.9 to 1.6, more preferably 1.0 to 1.4.
[0029] In a highly preferred embodiment, the solid sulfide electrolyte is of formula (II) Li 6 P.S. 5 X (II).
[0030] A preferred embodiment is a process according to the invention, wherein X=Cl, Br, I or a combination thereof, preferably X=Cl, Br or a combination thereof, more preferably X=Cl.
[0031] According to a preferred embodiment of the present invention there is provided a solid sulfide electrolyte, wherein at least 50 mol% of X represents Cl, preferably at least 80 mol% of X represents Cl, and most preferably X represents Cl.
[0032] According to a preferred embodiment of the present invention, there is provided a solid sulfide electrolyte, wherein X represents Cl, Br, I or a combination thereof, and at least 50 mol% of X represents Cl, preferably at least 80 mol% of X represents Cl.
[0033] According to a preferred embodiment of the present invention there is provided a solid sulfide electrolyte, wherein at least 50 mol% of X represents Br, preferably at least 80 mol% of X represents Br, and most preferably X represents Br.
[0034] According to a preferred embodiment of the present invention, there is provided a solid sulfide electrolyte, wherein X represents Cl, Br, I or a combination thereof, and at least 50 mol% of X represents Br, preferably at least 80 mol% of X represents Br.
[0035] According to a preferred embodiment of the present invention, there is provided a solid sulfide electrolyte, wherein at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I, and most preferably X represents I.
[0036] According to a preferred embodiment of the present invention, there is provided a solid sulfide electrolyte, wherein X represents Cl, Br, I or a combination thereof, and at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I.
[0037] A highly preferred embodiment is the process according to the invention, wherein X=Cl, Br or I, preferably X=Cl or Br, more preferably X=Cl.
[0038] A preferred embodiment is Li 2 S:Li 3 P.S. 4 In a more preferred embodiment, the molar ratio of Li to LiX is (0.5-1.5):(0.5-1.5):(0.5-1.5), preferably (0.75-1.25):(0.75-1.25):(0.75-1.25), and more preferably (0.9-1.1):(0.9-1.1):(0.9-1.1). 2 S:Li 3 P.S. 4 The molar ratio of LiX to Li is (0.95-1.05):(0.95-1.05):(0.95-1.05), preferably (0.98-1.02):(0.98-1.02):(0.98-1.02), and more preferably (0.99-1.01):(0.99-1.01):(0.99-1.01). In a highly preferred embodiment, Li 2 S:Li 3 P.S. 4 The molar ratio of LiX to Li is about 1:1:1.
[0039] A preferred embodiment is the method according to the present invention, wherein the molar ratios of Li:P:S:X are (5-7):(0.5-1.5):(4-6):(0.5-1.5), preferably (5.5-6.5):(0.75-1.25):(4.5-5.5):(0.75-1.25), and more preferably (5.75-6.25):(0.9-1.1):(4.75-5.25):(0.9-1.1). In a more preferred embodiment of the invention, the molar ratio of Li:P:S:X is (5.9-6.1):(0.95-1.05):(4.9-5.1):(0.95-1.05), preferably (5.95-6.05):(0.98-1.02):(4.95-5.05):(0.98-1.02), more preferably (5.98-6.02):(0.99-1.01):(4.98-5.02):(0.99-1.01). In a highly preferred embodiment, the molar ratio of Li:P:S:X is about 6:1:5:1.
[0040] A preferred embodiment is the method according to the invention, by mixing the solid electrolyte precursor mixture at a mixing speed of 1-1000 rpm, preferably 1-750 rpm, more preferably 1-500 rpm. According to a very preferred embodiment, the solid electrolyte precursor mixture is mixed at a mixing speed of 1-250 rpm, preferably 10-150 rpm, more preferably 50-100 rpm.
[0041] A preferred embodiment is a method according to the invention, wherein the mixing is carried out for a mixing time of at least 1 minute, preferably at least 0.5 hours, more preferably at least 1 hour, even more preferably at least 2 hours, even more preferably at least 5 hours, most preferably at least 10 hours. A preferred embodiment is a method according to the invention, wherein the mixing is carried out for a mixing time of less than 72 hours, preferably less than 60 hours, more preferably less than 50 hours, even more preferably less than 36 hours, even more preferably less than 30 hours, most preferably less than 24 hours. A preferred embodiment is a method according to the invention, by mixing the solid electrolyte precursor mixture for a mixing time of 1 hour to 72 hours, preferably 2 hours to 60 hours, more preferably 10 hours to 50 hours.
[0042] According to a highly preferred embodiment of the present invention, the mixing of the solid electrolyte precursor mixture comprises: A mixing speed of 1 to 250 rpm, preferably 10 to 150 rpm, more preferably 50 to 100 rpm, and The mixing time is from 1 hour to 72 hours, preferably from 2 hours to 60 hours, and more preferably from 10 hours to 50 hours.
[0043] As will be appreciated by those skilled in the art, in certain embodiments, the mixing of the solid electrolyte precursor mixture is equivalent to grinding, mechanically comminuting, pulverizing, milling or dry grinding the solid electrolyte precursor mixture. According to a preferred embodiment of the method, the mixing of the solid electrolyte precursor mixture of the present invention requires less energy to obtain a solid sulfide electrolyte after heat treatment.
[0044] A preferred embodiment is a method according to the present invention, in which the mixing of the solid electrolyte precursor mixture is carried out by using a mixing means, preferably the mixing means is a low energy mixing means, such as a ball mill, such as an electric ball mill, a vibrating ball mill, a planetary ball mill, a vibrating mixer mill or a SPEX mill, a bead mill, a homogenizer, a screw mixer, a horizontal mixer, a ploughshare mixer, a jar mill, a drum mill or a roller bench, more preferably the mixing means is a screw mixer, a horizontal mixer or a roller bench, most preferably a roller bench. In a particular embodiment, the mixing means is a non-planetary ball mill. As will be understood by those skilled in the art, a non-planetary ball mill is any ball mill that is not a planetary ball mill. Furthermore, a non-planetary ball mill is any ball mill that imposes low energy mixing on the solid electrolyte precursor mixture. In a more preferred embodiment, the mixing of the solid electrolyte precursor mixture is carried out by adding one or more ceramic or zirconia balls to the solid electrolyte precursor mixture to obtain a solid electrolyte mixture. As will be understood by those skilled in the art, the amount and size of the ceramic or zirconia balls are changed taking into account the total solid content of the solid electrolyte precursor mixture. As will be understood by those skilled in the art, after these ceramic or zirconia balls are removed from the solid electrolyte mixture, the solid electrolyte mixture is heat treated. According to a particular embodiment, the mixing means applies an inertial force of less than 38 G, preferably less than 25 G, more preferably less than 10 G to the solid electrolyte precursor mixture. According to a preferred embodiment, the mixing means applies an inertial force of more than 1 G, preferably more than 1.5 G, more preferably more than 2 G to the solid electrolyte precursor mixture. According to a preferred embodiment, the mixing means applies an inertial force of 1 G to 38 G, preferably 1.5 G to 25 G, more preferably 2 G to 10 G to the solid electrolyte precursor mixture.
[0045] A preferred embodiment is a process according to the invention, wherein the mixing is carried out at a temperature of at least 5° C., preferably at least 10° C., more preferably at least 15° C. A preferred embodiment is a process according to the invention, wherein the mixing is carried out at a temperature below 50° C., preferably below 40° C., more preferably below 30° C. A preferred embodiment is a process according to the invention, wherein the mixing is carried out at a temperature between 5 and 50° C., preferably between 10 and 40° C., more preferably between 15 and 30° C.
[0046] A preferred embodiment is a method according to the invention, wherein the heat treatment is carried out at a temperature of at least 100° C., preferably at least 200° C., more preferably at least 300° C., more preferably at least 400° C., even more preferably at least 450° C., most preferably at least 500° C. A preferred embodiment is a method according to the invention, wherein the heat treatment is carried out at a temperature below 1000° C., preferably below 900° C., more preferably below 800° C., even more preferably below 700° C., even more preferably below 600° C., most preferably below 550° C. A preferred embodiment is a method according to the invention, wherein the heat treatment is carried out at a temperature between 100 and 1000° C., preferably between 300 and 700° C., more preferably between 350 and 650° C.
[0047] As will be appreciated by those skilled in the art, the heat treatment of the solid electrolyte mixture to obtain a solid sulfide electrolyte having an argyrrhizite crystal structure is also referred to as calcining the solid electrolyte mixture towards the formation of argyrrhizite.
[0048] A preferred embodiment is a method according to the invention, wherein the heat treatment is carried out under an inert atmosphere, preferably under an argon atmosphere, or under an atmosphere comprising, preferably consisting of, hydrogen sulfide gas.
[0049] A preferred embodiment is a method according to the invention, wherein the heat treatment of the solid electrolyte mixture is for at least 1 minute, preferably at least 0.5 hours, more preferably at least 1 hour, even more preferably at least 1.5 hours, even more preferably at least 2 hours. A preferred embodiment is a method according to the invention, wherein the heat treatment of the solid electrolyte mixture is for less than 48 hours, preferably less than 24 hours, more preferably less than 18 hours, even more preferably less than 12 hours, even more preferably less than 10 hours. A preferred embodiment is a method according to the invention, wherein the heat treatment of the solid electrolyte mixture is for 0.5 hours to 24 hours, preferably 1 hour to 12 hours, more preferably 1.5 hours to 10 hours.
[0050] As understood in the context of the present invention, no additional liquid is added to the solid electrolyte precursor mixture, i.e., the solid electrolyte precursor mixture is not solubilized and / or dispersed in a liquid to facilitate the formation of a solid sulfide electrolyte. Thus, the present invention, in a highly preferred embodiment, provides a method for producing a solid sulfide electrolyte in a dry or solid state. In other words, the present invention provides a mechanical milling process for producing a solid sulfide electrolyte.
[0051] In one particular embodiment of the present invention, there is provided a method for producing a solid sulfide electrolyte, comprising the steps of: Li 2 S., Li 3 P.S. 4 and providing a set of precursors comprising LiX; mixing a set of precursors to obtain a solid electrolyte mixture; and heat treating the solid electrolyte mixture to obtain a solid sulfide electrolyte having a germanite crystal structure; wherein X is a halogen selected from F, Cl, Br, I, or combinations thereof.
[0052] As will be understood by those skilled in the art, all the above-mentioned embodiments apply mutatis mutandis to the above-mentioned certain embodiments of the present invention. Furthermore, the term "precursor set (solidified body)" as used herein refers to a composition that is essentially free of any liquid. The term "essentially free of liquid" means that the precursor set contains less than 10 wt% of the total weight of the precursor set, preferably less than 7.5 wt% of the total weight of the precursor set, more preferably less than 5 wt%, even more preferably less than 2.5 wt%, and most preferably less than 1 wt% of the liquid. In a more preferred embodiment, the precursor set contains less than 1000 ppm of the total weight of the precursor set, preferably less than 500 ppm of the total weight of the precursor set, more preferably less than 100 ppm of the liquid, even more preferably less than 50 ppm of the total weight of the precursor set, and most preferably less than 10 ppm of the liquid. In the context of the present invention, the terms "solid electrolyte precursor mixture" and "precursor set" are interchangeable terms, and the precursor Li 2 S., Li 3 P.S. 4 and LiX.
[0053] solid sulfide electrolyte A second aspect of the present invention provides a solid sulfide electrolyte obtainable by the method according to the present invention.
[0054] As will be understood by a person skilled in the art, all the embodiments relating to the method for producing a solid sulfide electrolyte according to the present invention apply equally to the solid sulfide electrolyte obtained by the method according to the present invention.
[0055] A preferred embodiment is Li as determined by XRD. 2 S, LiCl, Li 2 P.S. 3 and / or Li 3 P.S. 4 Substantially free of phases formed from Li 2 S, LiCl, Li 2 P.S. 3 and / or Li 3 P.S. 4 The peak intensity of Li 6 P.S. 5The solid sulfide electrolyte according to the present invention has a Cl peak intensity of less than 10%, preferably less than 8%, more preferably less than 5%, and most preferably less than 1%. According to a preferred embodiment, the solid sulfide electrolyte according to the present invention has a purity of at least 90% as determined by XRD, preferably at least 92%, more preferably at least 95%, and most preferably at least 99%.
[0056] A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of at least 0.25 mS / cm, preferably at least 0.5 mS / cm, more preferably at least 0.75 mS / cm, even more preferably at least 1 mS / cm, most preferably at least 1.5 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of less than 10 mS / cm, preferably less than 5 mS / cm, more preferably less than 2.5 mS / cm, even more preferably 2 mS / cm, most preferably 1.75 mS / cm. A preferred embodiment is a solid sulfide electrolyte according to the invention having an ionic conductivity of 0.25 to 10 mS / cm, preferably 0.5 to 5 mS / cm, more preferably 0.75 to 2.5 mS / cm.
[0057] A preferred embodiment is at least 1×10 -8 mS / cm, preferably at least 1×10 -7 mS / cm, more preferably at least 1×10 -6 A solid sulfide electrolyte according to the present invention has an electronic conductivity of 1×10 -2 Less than mS / cm, preferably 1×10 -3 mS / cm or less, more preferably 1×10 -4 A solid sulfide electrolyte according to the present invention has an electronic conductivity of less than 1×10 -8 ~1×10 -2 mS / cm, preferably 1×10 -7 ~1×10 -3 mS / cm, more preferably 1×10 -6 ~1×10 -4A solid sulfide electrolyte according to the present invention having an electronic conductivity of mS / cm.
[0058] A preferred embodiment is a solid sulfide electrolyte according to the present invention having an XRD pattern around 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1° and 32±1° using CuKα radiation.
[0059] battery A third aspect of the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the cathode, anode and solid electrolyte layer comprises a solid sulfide electrolyte according to the present invention.
[0060] As will be understood by those skilled in the art, a negative electrode is an anode and a positive electrode is a cathode. Thus, the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode and the solid electrolyte layer comprises a solid sulfide electrolyte according to the present invention.
[0061] The solid sulfide electrolyte of the present invention can be used as a solid electrolyte layer in a solid lithium ion battery or a solid lithium primary battery, or as a solid electrolyte mixed with an electrode mixture for a positive or negative electrode.
[0062] In a preferred embodiment, the battery is a solid state battery, preferably a lithium solid state battery.
[0063] use A fourth aspect of the present invention relates to the use of the solid sulfide electrolyte according to the present invention in a battery, preferably a solid-state battery, more preferably a lithium solid-state battery.
[0064] A fifth aspect of the invention relates to the use of a battery according to the invention in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle, preferably in any one of an electric vehicle or a hybrid electric vehicle.
[0065] The invention is further illustrated in the following examples. EXAMPLES
[0066] Test method description XRD analysis XRD experiments were carried out using a Panalytical X'Pert Pro with a Cu Kα1 source (1.5405980 A or 8.05 keV). The sample holder was an Anton Paar holder with a PEEK dome. The software used for the analysis was Highscore.
[0067] Ionic Conductivity Ionic conductivity was measured using electrochemical impedance spectroscopy (EIS) at room temperature (25 °C) on cold-pressed samples in a pellet cell with an ion-blocking electrode. The samples are densified at 350 MPa. Ionic conductivity is measured under an operating pressure of 125 MPa. For EIS, an excitation voltage of 10 mV is applied in the frequency range of 7 MHz to 1 Hz. Measurements are performed using a potentiostat equipped with a frequency analyzer. Data are interpreted by equivalent circuit analysis.
[0068] Electronic Conductivity The electronic conductivity is measured on the same samples as the ionic conductivity (125 MPa, RT) by step potentiostatic polarization for 20 min at 0.2 V, 0.4 V and 0.6 V. The measurements are carried out using a potentiostat equipped with a frequency analyzer.
[0069] Example 1 Lithium sulfide (Li 2 S, 6.8 g), lithium chloride (LiCl, 6.9 g) and lithium thiophosphate (Li 3 P.S. 4A mixture containing 100% Li, 27g of lithium sulphide, 100% lithium chloride and 100% lithium thiophosphate was prepared. The mixture was filled into a plastic container with steatite balls of 6 mm diameter. The weight of the balls was 400 g. The plastic bottle or container was placed on a roller bench for 24 hours at a temperature of 25° C. The roller bench generates the energy required for mixing the mixture of lithium sulphide, lithium chloride and lithium thiophosphate. The specifications of the roller bench are shown in Table 1. The mixture was then transferred to a muffle furnace and heat treated at 525° C. by using a heating gradient of 1° C. / min up to 525° C., held at 525° C. for 8 hours, and subsequently cooled to room temperature, thereby obtaining a solid sulphide electrolyte. The solid sulphide electrolyte was subjected to XRD analysis (see FIG. 2), which showed that the solid sulphide electrolyte contained 93% Li 6 P.S. 5 Cl and 7% Li 2 The ionic and electronic conductivities of the solid sulfide electrolyte were 1.5 mS / cm and 2.05 × 10 -4 mS / cm. [Table 1]
[0070] Example 2 Lithium sulfide (Li 2 S, 25.7 g), lithium chloride (LiCl, 26.1 g) and lithium thiophosphate (Li 3 P.S. 4 A mixture containing 100.7 g of lithium sulfide, 100.7 g of lithium chloride and 100.7 g of lithium thiophosphate was prepared. The mixture was filled into a plastic container with steatite balls of 10 mm diameter. The weight of the balls is 2 kg. The plastic bottle or container is placed on a roller bench for 48 hours at a temperature of 25° C. The roller bench generates the energy required for mixing the mixture of lithium sulfide, lithium chloride and lithium thiophosphate. The specifications of the roller bench are shown in Table 1. The mixture was then transferred to a muffle furnace and heat treated at 530° C. by using a heating gradient of 1° C. / min up to 530° C., held at 530° C. for 2 hours, and subsequently cooled to room temperature, thereby obtaining a solid sulfide electrolyte. The solid sulfide electrolyte was subjected to XRD analysis (see FIG. 3), which showed that the solid sulfide electrolyte contained 92% Li. 6 P.S.5 Cl, 5% Li 2 S, and 3% LiCl.
[0071] Example 3 Lithium sulfide (Li 2 S, 2.1 g), lithium chloride (LiCl, 0.8 g) and phosphorus pentasulfide (P 2 S 5 A mixture containing 100% Li, 2.1 g of lithium sulphide, 100% lithium chloride and 100% lithium thiophosphate was prepared. The mixture was packed in a plastic container with steatite balls of 6 mm diameter. The weight of the balls is 47.7 g. The plastic bottle or container is placed on a roller bench for 48 hours at a temperature of 25° C. The roller bench generates the energy required for mixing the mixture of lithium sulphide, lithium chloride and lithium thiophosphate. The specifications of the roller bench are shown in Table 1. The mixture was then transferred to a muffle furnace and heat treated at 00° C. by using a heating gradient of 1° C. / min up to 500° C., held at 500° C. for 6 hours, and subsequently cooled to room temperature, thereby obtaining a solid sulfide electrolyte. The solid sulfide electrolyte was subjected to XRD analysis (see FIG. 4), which showed that the solid sulfide electrolyte contained 58% Li 6 P.S. 5 Cl, 20% Li 2 S and 22% Li 2 P.S. 3 The ionic and electronic conductivities of the solid sulfide electrolyte are 0.1 mS / cm and 4.4 × 10 -5 mS / cm.
[0072] Example 4 A test cell was prepared by pressing 100 mg of the solid sulfide electrolyte obtained in Example 1 in a Teflon 10 mm die at 2 tons to form a separator. A cathode disk consisting of NMC811, conductive carbon, and the solid sulfide electrolyte obtained in Example 1 in a mass ratio of 63:3:33, PTFE by weight, and a LiIn alloy disk were added on both sides of the separator. All cell components were compressed and the compressed cell was sealed with a sealing sleeve. The cell was cycled in a climatic chamber at 60° C. FIG. 5 represents the first charge-discharge curve. FIG. 6 illustrates the rate capability test.
Claims
1. A method for producing a solid sulfide electrolyte, comprising: Li 2 S., Li. 3 P.S. 4 providing a solid electrolyte precursor mixture comprising LiX and mixing the solid electrolyte precursor mixture to obtain a solid electrolyte mixture; and heat treating the solid electrolyte mixture to obtain a solid sulfide electrolyte having a germanite-type crystal structure. wherein X is a halogen selected from F, Cl, Br, I, or a combination thereof.
2. The solid sulfide electrolyte is represented by the formula (I) Li 7-y P.S. 6-y X y (I) In the formula, y is 0.8 to 1.7, preferably y is 0.9 or more and 1.6 or less, and more preferably y is 1.0 or more and 1.4 or less. The method for producing a solid sulfide electrolyte according to claim 1.
3. The solid sulfide electrolyte is represented by the formula (II) Li 6 P.S. 5 The method for producing the solid sulfide electrolyte according to claim 1 , wherein X (II) is
4. 2. A method for producing the solid sulfide electrolyte according to claim 1, by mixing the solid electrolyte precursor at a mixing speed of 1-250 rpm, preferably 10-150 rpm, more preferably 50-100 rpm.
5. The method for producing a solid sulfide electrolyte according to claim 1, wherein the mixing of the solid electrolyte precursor mixture is carried out for a mixing time of 1 hour to 72 hours, preferably 2 hours to 60 hours, more preferably 10 hours to 50 hours.
6. Li 2 S: Li 3 P.S. 4 2. The method for producing a solid sulfide electrolyte according to claim 1, wherein the molar ratio of Li:LiX is 1:1:
1.
7. 2. The method for producing a solid sulfide electrolyte according to claim 1, wherein X=Cl, Br, I or a combination thereof, more preferably X=Cl, Br or a combination thereof, and most preferably X=Cl.
8. The method for producing a solid sulfide electrolyte according to claim 1, wherein the heat treatment is carried out at a temperature of 100 to 1000 ° C, preferably at a temperature of 300 to 700 ° C, more preferably at a temperature of 350 to 650 ° C.
9. The method for producing a solid sulfide electrolyte according to claim 1, wherein the heat treatment is carried out for 0.5 hours to 24 hours, preferably 1 hour to 12 hours, and more preferably 1.5 hours to 10 hours.
10. The method for producing a solid sulfide electrolyte according to claim 1 , wherein the heat treatment is carried out in an inert atmosphere or an atmosphere containing hydrogen sulfide gas.
11. The method for preparing the solid sulfide electrolyte according to claim 1, wherein the mixing is carried out by using a ball mill, a bead mill, a homogenizer, a horizontal mixer, a plowshare mixer, a screw mixer, a jar mill, a drum mill or a roller bench, preferably a roller bench.
12. A solid sulfide electrolyte obtainable by the method of claim 1.
13. an ionic conductivity of greater than 0.1 mS / cm, preferably greater than 1 mS / cm, more preferably greater than 1.25 mS / cm, and / or greater than 1×10 -2 Less than mS / cm, preferably 1×10 -3 mS / cm or less, more preferably 1×10 -4 13. The solid sulfide electrolyte of claim 12 having an electronic conductivity of less than mS / cm.
14. 13. The solid sulfide electrolyte of claim 12 having a purity of at least 90% as determined by XRD.
15. 15. A battery comprising a negative electrode, a positive electrode, and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer comprises the solid sulfide electrolyte according to any one of claims 12 to 14.
Citation Information
Patent Citations
Sulfide-based solid electrolyte composition
JP2013143338A
Method for producing sulfide solid electrolyte having argyrodite type crystal structure
JP2018206774A
Methods for wet chemical synthesis of lithium argyrodites and enhancing interface stability
US20220093967A1
Solid electrolyte and method for producing same
WO2021054433A1